CORRELATION BETWEEN PSYCHOLOGICAL WELL-BEING AND LEVEL OF RELIGIOSITY MANIFESTATION AT DIFFERENT AGES - Telepova, Nadezhda; Telepov, Mikhail (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The influence of modern society non-stability due to different reasons (political, economic, epidemiological etc.) on people’s well-being, mood and health is obvious. The objective of the study is the correlation between psychological well-being and religiosity manifestation of people at different ages. In our research we set the aim of studying and revealing the dynamics of correlation between these two categories while aging. Hypothesis of our research is that there is a dynamic of correlation associations while aging and there is strong positive association between psychological well-being and religiosity manifestation at second part of middle age and old age. We take religiosity as a deep personal structure, existential attitude which cannot be limited by definite religious confession but can be measured by manifestation factors. We conducted our research on the basis of Samara Methodist Church in 2018-2020. The sample includes 85 people, among them 22 at the age of 20-24(early adulthood), 20 at the age of 25-50(first part of middle age), 21 at the age of 51-64(second part of middle age, preretirement period), 18 at the age of 65-85 (old age). Study methods: observation, conversation, “Psychological well-being scales by Carol Ryff”, authors’ “questionnaire on religiosity manifestation”, methods of mathematical statistics (Spearman's correlation coefficient). Analyzing the dynamics of the correlation between level of religiosity manifestation and psychological well-being we revealed that while aging there are quite different correlation data. There is no statistically significant association between General Index of Psychological well-being and level of religiosity manifestation at the ages of early adulthood and first part of middle age, but in the groups of participants of second part of the middle age and old age there is strong positive correlation.